A Prática Docente Durante A Pandemia: O Caso Da Escola Família Agrícola De Porto Nacional-To - SILVA, Laissa Teles Da (Universidade Federal do Tocantins, 2023)
This study evaluated the teaching practice during the pandemic, the case of the agricultural family school of Porto Nacional -TO. This study aimed to analyze the teaching practice in school and what were the greatest challenges faced during the pandemic, to understand the difficulties and strategies of teachers focused on the teaching model adopted for the school of the field. For this study, an interview was used to collect data from a semi-structured script. The study has a qualitative, descriptive approach, where a prerequisite adopted for the choice of participants was educational follow-up during the pandemic process. The interviews were conducted in person at the school, recorded and later transcribed. We analyzed the teachers' discourse on pedagogical practice during the pandemic, to understand the greatest challenges in relation to access to technologies and the challenges and adaptations of teachers during the pandemic period. The results indicated limitations in access to the Internet by students, which directly reflects in teaching practice, because it prevents the interaction between teacher and student that is essential in the teaching and learning process. Thus, for the success of remote education focused on rural areas, it is necessary to propose teaching strategies so that they can advance equally, in addition to a planning that precedes adequate training for teachers to deal with a new teaching model previously not carried out by them.